Presentation Software Tools in Higher Educational Setting - Elizaveta Osipovskaya; Elena Burdovskaya (ARPHA Proceedings, 2019)
The article deals with the issue of introducing PowerPoint alternatives (Google Slides, Prezi, Tilda, Slides, Haiku Deck) for creating animated presentations. Much remains unknown about general attitudes toward presentation software tools and other online services or users’ functional demands other than editing texts, resizing and color-correcting images. Thus, we focused on users’ experience, advantages and disadvantages of such tools, including the comparison amid public relations students of RUDN University and employers in various fields of industry. The survey was conducted among users of presentation software. The groups of public relations students of RUDN University and public relations professionals who were asked to participate in this study which included 93 volunteers. The online questionnaire was divided in three topics: 1) the use of presentation software (purpose, frequency of use), 2) the use of multimedia options and export formats (import of images, videos, audio content, tables), 3) the use of additional presentation software options and other properties (loading speed, animation effects, panoramic images, 360-degree videos). Moreover, the participants were invited to bring forward the proposals for presentation software in open-ended questions. The findings reveal that PowerPoint is increasingly used by the employees to create visual documents (slideshows) or handouts that are intended to be read and referenced instead of projecting. It is found that the most frequently used software is Google Slides (71%) and Prezi (24%). It is undoubtedly that the results of our study could help developers to improve online presentation tools or to create new ones.